COVID-19 Pandemic is a renewed call for 'Speaking Up for Hand Hygiene' - Mohd Ali, Noor Azizah; Thudawe, Yohani Shavindi Dalugoda; Ballard, Emma L.; Jauncey-Cooke, Jacqueline; Bogossian, Fiona (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd., 2020)
As of the 31st July 2020, more than 17 million confirmed COVID-19 cases with over 668k deaths have been reported worldwide (World Health Organisation (WHO), 2020). The COVID-19 virus is genetically similar to the Severe Acute Respiratory Syndrome (SARS) and the Middle East Respiratory Syndrome (MERS) (Schmidt, Davids, & Malinga., 2020; Zhao et al., 2020). However, initial investigations of the basic reproduction number (Ro) of COVID-19 shows higher transmissibility than SARS and MERS (Zhao et al.,2020). The mode of transmission of COVID-19 is mainly through close contacts via droplets from human to human (World Health Organisation (WHO), 2020). Whilst researchers around the world are focused on developing a vaccine for COVID-19, transmission preventative measures become the most effective means of response.